La organización hipertextual del ordenamiento jurídico. Posibilidades de XML y estándares relacionados - Arellano Pardo, Mª del Carmen; Nogales Flores, José Tomás; Martín Galán, Bonifacio (Revista General de Información y Documentación, 2003)
The capabilities of XML and associated standards (XLink, XPointer, XPath, XSLT...) for treatment, storage and access to legislative texts are presented. This type of document does not have to be interpreted separately, but as a set of documents, the legal system, in continuous growth like a reflection of the changes in the societies that it regulates, including new regulation or modifying the already existing one. The capabilities of the new standards of linking for XML documents and the possibilities of reusability of the information marked is revealed as a suitable solution to correctly define the complexity of hypertextual organization as a reflection of the relations of different kind (links) that occur between the different norms (nodes) that compose the legal system.